A meta-analysis on anti-fungal drug efficacy in patients with oropharyngeal candidiasis in immunocompromised patients - Osamah Soliman Al Alawi; Ahmed Shaker Ali; Duaa Bakhshwin; Fahad Hameed Aljahdali (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Oropharyngeal candidiasis (OPC) is fungal infection caused by Candida albicans. Aim: To compare the efficiency of different antifungal drugs in the management of oropharyngeal candidiasis in immunocompromised cases. Patients & methods: Fifteen investigation have been involved in this systematic review and meta-analysis, with 3646 immunocompromised patients with soph pharynx geal or oropharyngeal candidiasis. In all studies, cases have been assigned to receive Fluconazole, Nystatin, Anidulafungin, Itraconazole, or a placebo. Two authors independently searched online databases including EMBASE, Scopus MEDLINE, Cochrane Library, PubMed, and Web of Science Results: Regarding the assessment of Microbiological Success for different antifungal drugs, fluconazole showed RR with 95% CI: 0.53 [0.35,0.7], A random effect model was applied, and heterogeneity was detected among our pooled studies with chi-p<0.001 and I2 =97%. The rate of adverse events for fluconazole were (22.8%) lower than that for itraconazole (64.5%) and micafungin (54.8%), and most adverse events were mild elevation of transaminase levels, gastrointestinal symptoms, and oral burning sensation. Our pooled studies for this outcome were heterogeneous; therefore, a random-effects model was applied with a chi-p=0.001 and I2=100%. Our pooled studies for mortality rate reported RR with 95%CI ,0.09 [0.05, 0.13] and, 0.1 [-0.016, 0.232] for fluconazole and itraconazole, respectively. Conclusion: Fluconazole is recommended as an antifungal agent for oropharyngeal candidiasis in immunosuppressed cases, as it was effective in producing a successful clinical outcome and had reasonable safety compared to antifungal agents.